High precision characterization of RCCX rearrangements in a 21-hydroxylase deficiency Latin American cohort using oxford nanopore long read sequencing - Claps, Aldana (2025)
The CYP21A2 gene, mapped to the RCCX module in 6p21.3, is responsible for 21-hydroxylase deficiency (21-HD). In this work, we leveraged Oxford Nanopore Technology (ONT) Long Read sequencing (LRS) to analyze samples from an Argentinian cohort of 21-HD. A total of 34 samples were sequenced in 2 amplicons of 8.5 Kb covering the centromeric and telomeric RCCX modules. The number of variants found varied between 3 and 106 and all expected pathogenic variants and new ones were obtained with the LR sequencing workflow developed. We defined with higher accuracy the breakpoints of the rearrangements allowing the reclassification of chimeras and/or converted genes in 18.75% of the samples, some of them with clinical implications. By addressing the study of the telomeric RCCX module/s in depth, we found 19 genetic variants (GVs) for CYP21A1P and 29 GVs for TNXA not previously described in Latin American populations. This study may represent the first application of ONT LRS for clinical evaluation of Latin American subjects, highlighting the importance of LRS as a high-resolution method of diagnosis. It would allow a better understanding of the diversity of the RCCX modules and improve our knowledge of the variation of genetic mechanisms behind the disease.